TabTech - Yazeed, Hanani Bahiyah; Adi Barkhiar, Nurqaisara Khalishah Hana; Abu Sapian, Alieya Syahierah; Md Shaiful Azman, Nur Adriana Fasiha; Nik Zuraidi, Nik Nurul Atiyah; Akhyani, Nur Atiqah (2025)
In today’s digital era, students are increasingly disengaged from educational tools like textbooks, creating a need for more interactive and personalized learning experiences. TabTech is a technology enhanced educational assistant that combines a smart tablet with an ergonomically designed table to support both teaching and learning. Aimed at primary and secondary students, TabTech offers an intuitive platform where learners can complete interactive quizzes, access multimedia lessons, and receive instant, personalized feedback. Students sit at an ergonomic table with an integrated tablet, logging in with personal credentials to access a customized learning environment. The system adapts content difficulty based on each student’s progress and includes accessibility features such as adjustable screen settings to support vision difficulties or specific learning preferences. It also restricts access to distracting or inappropriate content, helping students maintain focus safely. The combined table-and-tablet setup promotes better posture, reduces eye strain, and supports visual learners through rich, interactive content. For teachers, TabTech provides a real-time dashboard accessible on various devices to assign lessons and quizzes tailored to their curriculum, monitor student progress and engagement, and analyze detailed performance data to identify students needing additional support or enrichment. The platform helps maintain classroom focus through content controls and allows teachers to generate reports for tracking academic outcomes and facilitating communication with students, parents, and administrators. Designed for classrooms and blended learning environments, TabTech offers flexibility and accessibility. Based on research on similar educational technologies, TabTech is expected to enhance engagement, improve focus, and contribute to better academic outcomes by fostering active learning and providing valuable insights for teachers.